Case report: Clinical characteristics of two cases of pneumonia caused with different strains of Chlamydia psittaci - Wang, Zheng; Chen, Chen; Lu, Hu; Wang, Li; Gao, Lin; Zhang, Jing; Zhu, Chi; Du, Furong; Cui, Lunbiao; Tan, Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Underdiagnosis of Chlamydia psittaci (C. psittaci) infection in China is possible due to lack of awareness by physicians. The pneumonia caused by C. psittaci may be life-threatening. C. psittaci can be classified into 15 genotypes. Here, we reported 2 genotypes SZ18-2 and SZ15 of C. psittaci which were rarely infected in human, and analyzed the clinical manifestations and changes in laboratory indicators of two patients. Case presentation: Case 1: A 66-year-old male farmer who fed ducks presented to hospital for cough, diarrhea and lethargy with the temperature of 39.8℃. Case 2: A 48-year-old male worker who slaughtered ducks was transferred to hospital for high fever, cough, generalized muscle ache, diarrhea and loss of appetite for 5 days. Both patients did not take any protective measures (wearing face masks or gloves) while processing ducks. C. psittaci pneumonia was diagnosed by metagenomic next-generation sequencing. After treatment with doxycycline and azithromycin individually, they recovered well and discharged from the hospital. Through OmpA sequencing, two different genotypes (SZ18-2 and SZ15) were identified in case 1 and case 2, respectively. Conclusion: Patients infected C. psittaci of different genotypes may own different clinical manifestations. C. psittaci infection should be suspected when pneumonia appears, accompanied by digestive symptoms and multiple organ dysfunction, especially under the exposure of specific birds.